Urinary Extracellular Vesicle: A Potential Source of Early Diagnostic and Therapeutic Biomarker in Diabetic Kidney Disease - Wei-Cheng Xu; Ge Qian; Ai-Qun Liu; Yong-Qiang Li; He-Qun Zou (Chinese Medical Journal, 2018)
Objective: Diabetic kidney disease (DKD) has become one of the major causes of end-stage renal disease. Urinary extracellular vesicles (uEVs) contain rich biological information which could be the ideal source for noninvasive biomarkers of DKD. This review discussed the potential early diagnostic and therapeutic values of proteins and microRNAs in uEVs in DKD. Data Sources: This review was based articles published in PubMed, Embase, Cochrane, and Google Scholar databases up to November 20, 2017, with the following keywords: “Diabetic kidney disease”, “Extracellular vesicle”, and “Urine”. Study Selection: Relevant articles were carefully reviewed, with no exclusions applied to the study design and publication type. Results: There is no “gold standard” technology to separate and/or purify uEVs. The uEVs contain a variety of proteins and RNAs and participate in the physiological and pathological processes of the kidney. UEVs, especially urinary exosomes, may be useful biomarkers for early diagnosis and treatment to DKD. Furthermore, the uEVs has been used as a therapeutic target for DKD. Conclusion: Proteins and nucleic acids in uEVs represent promising biomarker for the diagnosis and treatment of DKD.